Environmental regulation and sustainable competitiveness: Evaluating the role of firm-level green investments in the context of the Porter hypothesis - Jana Stoever; John P. Weche (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2015)
We investigate the impact of environmental regulation on firm performance and investment behavior. Exploiting the case of a German water withdrawal regulation that is managed on the state level, we analyze firms' reactions to an increase in the water tax using a regression- adjusted difference-in-differences approach. We analyze the individual firm's response to a change in environmental regulation, distinguishing between add-on and integrated environ- mental investments. This allows us to include intra-firm innovations into our analysis, which are likely to be of importance for increasing resource-efficiency. Our results show that the regulation in question shows no sign of affecting firms' overall competitiveness. The results imply that the predicted negative impact of the regulation on firms' economic performance that was brought up before the introduction of the tax, does not seem to weigh heavily in this case. Nevertheless, when placed into a sustainable competitiveness context, the regulation considered does not qualify as an appropriate policy tool for fostering green growth.
Keywords: L60; O31; O32; Q58; Q55; 330; environmental regulation; DID; green growth; green investment; Porter hypothesis; sustainable competitiveness; water withdrawal regulation